Central interaction between atrial natriuretic peptide and angiotensin II in the control of sodium intake and excretion in female rats - De-Angelis, P. R. [UNESP]; Antunes, V. R. [UNESP]; Camargo, G. M.P.A. [UNESP]; Saad, W. A. [UNESP]; Renzi, A. [UNESP]; Camargo, L. A.A. [UNESP] (My University, 1996)
We investigated the effects of estrogen on sodium intake and excretion induced by angiotensin II (ANG II), atrial natriuretic peptide (ANP) or ANG II plus ANP injected into the median preoptic nucleus (MnPO). Female Holtzman rats weighing 250-300 g were used. Sodium ingestion and excretion 120 min after the injection of 0.5 μl of 0.15 M NaCl into the MnPO were 0.3 ± 0.1 ml (N = 12) and 29 ± 7 μEq in intact rats, 0.5 ± 0.2 ml (N = 10) and 27 ± 6 μEq in ovariectomized rats, and 0.2 ± 0.08 (N = 11) and 36 ± 8 μEq in estrogen-treated ovariectomized (50 μg/day for 21 days) rats, respectively. ANG II (21 μM) injection in intact, ovariectomized, and estrogen-treated ovariectomized rats increased sodium intake (3.8 ± 0.4, 1.8 ± 0.3 and 1.2 ± 0.2 ml/120 min, respectively) (N = 11) and increased sodium excretion (166 ± 18,82 ± 22 and 86 ± 12 μEq/120 min, respectively) (N = 11). ANP (65 μM) injection in intact (N = 11), ovariectomized (N = 10) and estrogen-treated ovariectomzed (N = 10) rats increased sodium intake (1.4 ± 0.2, 1.8 ± 0.3, and 1.7 ± 0.3 ml/120 min, respectively) and sodium excretion (178 ± 19, 187 ± 9, and 232 ± 29 μEq/120 min, respectively). Concomitant injection of ANG II and ANP into the MnPO of intact (N = 12), ovariectomized (N = 10) and estrogen-treated ovariectomized (N = 10) rats caused smaller effects than those produced by each peptide given alone: 1.3 ± 0.2, 0.9 ± 0.2 and 0.3 ± 0.1 ml/120 min for sodium intake, respectively, and 86 ± 9,58 ± 7, and 22 ± 4 μEq/120 min for sodium excretion, respectively. Taken together, these results demonstrate that there is an antagonistic interaction of ANP and ANG II on sodium intake and excretion, and that reproductive hormones affect this interaction.
Keywords: angiotensin II; atrial natriuretic peptide; ovariectomy; sodium excretion; sodium intake